2020
DOI: 10.1186/s12872-020-01662-3
|View full text |Cite|
|
Sign up to set email alerts
|

Admission fasting plasma glucose is associated with in-hospital outcomes in patients with acute coronary syndrome and diabetes: findings from the improving Care for Cardiovascular Disease in China - Acute Coronary Syndrome (CCC-ACS) project

Abstract: Background: The discrepancy between glycosylated hemoglobin (HbA 1c) and fasting plasma glucose (FPG) in clinical practice may be related to factors such as acute stress, renal dysfunction, and anemia, and its relationship with in-hospital outcomes is uncertain. The aim of this study was to investigate the association between the type of discrepancy between HbA 1c and FPG and in-hospital outcomes in patients with acute coronary syndrome (ACS) and diabetes. Methods: The Improving Care for Cardiovascular Disease… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(32 reference statements)
0
4
0
1
Order By: Relevance
“…Considering the definition of FG used in these studies, it seems to be an alternative index for ABG. However, FG within 24 h of admission was reported to be associated with both increased short and long-term mortalities only in diabetic patients with ACS ( 31 33 ).…”
Section: Defining Sih In the Context Of Acsmentioning
confidence: 99%
“…Considering the definition of FG used in these studies, it seems to be an alternative index for ABG. However, FG within 24 h of admission was reported to be associated with both increased short and long-term mortalities only in diabetic patients with ACS ( 31 33 ).…”
Section: Defining Sih In the Context Of Acsmentioning
confidence: 99%
“…Given such diverse study findings, the most appropriate glycemic status indicator remains to be established. Some answers come from a Chinese study of 7762 patients with ACS and diabetes that looked at patients with inconsistencies between the two most common parameters used to determine glycemic status, namely FPG and HbA1c [ 47 ]. Inconsistencies were defined as either both HbA1c ≥ 48 mmol/mol and FPG < 7.0 mmol/L, or both HbA1c < 48 mmol/mol and FPG ≥ 7.0 mmol/L.…”
Section: Resultsmentioning
confidence: 99%
“…The study showed that inconsistencies in FPG and HbA1c levels result in two patient categories with different in-hospital outcomes. After adjusting for confounding factors, patients in the increased FPG group were more likely to suffer adverse CV outcomes compared with those in the increased HbA1c group [ 47 ]. Thus, in the setting of ACS, among diabetic patients with HbA1c-FPG discrepancy, those with increased FPG are at a higher risk of in-hospital adverse outcomes compared to those with increased HbA1c [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Semua penelitian ini menggunakan sampel manusia (Tabel 2). [12][13][14][15][16][17][18][19][20] Pembahasan Kadar gula darah yang tidak terkontrol pada pasien DM tipe 2 berkaitan dengan metabolisme glukosa yang abnormal yang dapat meningkatkan kecepatan pembentukan plak aterosklerosis yang kemudian mengalami trombosis dan ruptur, serta gangguan fungsi endotel yang menyebabkan jejas pada pembuluh darah. 15,21,22 Beberapa penelitian yang telah di-review secara teliti menunjukkan bahwa kadar gula darah tidak terkontrol merupakan presentasi yang umum di kalangan pasien dengan infark miokardiak akut dan dapat menurunkan fungsi sistolik, sampai mengarah kepada hal yang fatal, yaitu kematian.…”
Section: Hasilunclassified